ANACIM Mobile App User Manual - Annaiah, Akshatha Billava (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The AICCRA-ANACIM is an android-based mobile application developed in collaboration with the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), International Livestock Research Organization (ILRI) and, the CGIAR initiative on digital innovation (CGIAR-DI) worked closely with the Senegal's national meteorological services (ANACIM). The AICCRA-ANACIM is a simple and user-friendly application that is designed to minimize unintentional data collection errors. This app helps to collect data from the agriculture & allied sectors such as Agriculture, Livestock, Market, Fish and, Forestry. The app also enables the Multidisciplinary Working Group of the National Framework of the Climate Service (GTP users) to collect agro-meteorological data such as weather and, water points from various agrarian regions of Senegal. The AICCRA-ANACIM app is a multilingual, available in both English & French version. The data collected via mobile app is uploaded to a cloud-based system in real-time and presented on a web dashboard.